(untitled) (Medical Forum Monthly, 2024)
Objective: To study the effects of electromagnetic radiations on follicles of Thyroid gland of mice. Study Design: Laboratory based randomized controlled trials. Place and Duration of Study: The study was carried out in department of Anatomy, Army Medical College Rawalpindi in collaboration with National Institute of Health, Islamabad from November 2009 to November 2010. Materials and methods: Twenty adult Balb/C male mice were divided randomly into two study groups, comprising of 10 animals in each group.Group A was kept under experimental conditions without mobile phone exposure, group B exposed to radiations for 1 hour /day, for two months from mobile phone set. Thyroid glands were removed and sectioned after exposure period. Sections were stained with hematoxylin and eosin for microscopic examination. Results: Results showed statistically significant difference in number and mean size of Thyroid follicles in gland of experimental groups. Conclusion: Thus it is concluded that exposure to EMFs causes decrease in size and increase in number of follicles of thyroid gland of mice, indicating hyperactivity of gland.